PERLINDUNGAN UPAH PEKERJA TETAP DAN PEKERJA HARIAN DITINJAU DARI KEPMENAKERTRANS NOMOR 17 TAHUN 2005 TENTANG KOMPONEN PELAKSANAAN PENCAPAIAN KEBUTUHAN HIDUP LAYAK - Joko Pitoyo (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACT In Indonesia, the payment policy of low wages for workers already a comparative advantage offered by the government to investors or investors, investors both local and foreign investors that are interested to invest in Indonesia. it can be seen from the use of standard Physical Requirements Minimum (KFM) of a single worker in the calculation of the minimum wage in 1956 era. Often, however, the minimum wage is far below the KFM count. In 1991 for example, the wages of workers only reached 60% of the value of KFM, even in practice, many employers who pay their workers wages below the official minimum wage standards that have been set, plus the absence of legal provisions that impose sanctions for violations of minimum wage.